Exercise and children's cognition: The role of exercise characteristics and a place for metacognition - Phillip D. Tomporowski; Bryan McCullick; Daniel M. Pendleton; Caterina Pesce (Elsevier, 2015)
Definitive conclusions concerning the impact of exercise interventions on children's mental functioning are difficult to ascertain because of procedural differences among studies. A narrative review of studies was conducted to evaluate the role of two types of exercise interventions on children's cognition. Acute and chronic exercise interventions were classified as quantitative or qualitative on the basis of manipulations of task complexity and, by inference, mental engagement. Both types of interventions enhance aspects of children's cognition; however, their effects on metacognitive processes are unknown. The role of metacognitive processes and their regulation of children's behavior and academic performance are highlighted.